Expanding radiotherapy access in Sub-Saharan Africa: an analysis of travel burdens and patient-related benefits of hypofractionation - Patel, Saloni; Olatunji, Elizabeth; Mallum, Abba; Benjika, Binsila Bernard; Joseph, Adedayo O.; Joseph, Shomari; Lasebikan, Nwamaka; Mahuna, Habiba; Ngoma, Mamsau; Ngoma, Twalib Athumani; Nnko, Godwin; Onwualu, Chinelo; et al. (Frontiers in Oncology, 2023)
Purpose The purpose of this project was to examine the travel burdens for radiotherapy patients in Nigeria, Tanzania, and South Africa, and to assess the patient-related benefits of hypofractionated radiotherapy (HFRT) for breast and prostate cancer patients in these countries. The outcomes can inform the implementation of the recent Lancet Oncology Commission recommendations on increasing the adoption of HFRT in Sub-Saharan Africa (SSA) to enhance radiotherapy access in the region. Methods Data were extracted from electronic patient records at the NSIA-LUTH Cancer Center (NLCC) in Lagos, Nigeria and the Inkosi Albert Luthuli Central Hospital (IALCH) in Durban, South Africa, from written records at the University of Nigeria Teaching Hospital (UNTH) Oncology Center in Enugu, Nigeria, and from phone interviews at Ocean Road Cancer Institute (ORCI) in Dar Es Salaam, Tanzania. Google Maps was used to calculate the shortest driving distance between a patient’s home address and their respective radiotherapy center. QGIS was used to map the straight-line distances to each center. Descriptive statistics were used to compare transportation costs, time expenditures, and lost wages when using HFRT versus conventionally fractionated radiotherapy (CFRT) for breast and prostate cancer. Results Patients in Nigeria (n=390) traveled a median distance of 23.1 km to NLCC and 86.7 km to UNTH, patients in Tanzania (n=23) traveled a median distance of 537.0 km to ORCI, and patients in South Africa (n=412) traveled a median distance of 18.0 km to IALCH. Estimated transportation cost savings for breast cancer patients in Lagos and Enugu were 12,895 Naira and 7,369 Naira, respectively and for prostate cancer patients were 25,329 and 14,276 Naira, respectively. Prostate cancer patients in Tanzania saved a median of 137,765 Shillings in transportation costs and 80.0 hours (includes travel, treatment, and wait times). Mean transportation cost savings for patients in South Africa were 4,777 Rand for breast cancer and 9,486 Rand for prostate cancer. Conclusion Cancer patients in SSA travel considerable distances to access radiotherapy services. HFRT decreases patient-related costs and time expenditures, which may increase radiotherapy access and alleviate the growing burden of cancer in the region.